2022
DOI: 10.3390/biomedicines10092142
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Viral Vectors for Therapeutic Programming of Tumour Microenvironment: Advantages and Limitations

Abstract: Viral vectors have been widely investigated as tools for cancer immunotherapy. Although many preclinical studies demonstrate significant virus-mediated tumour inhibition in synergy with immune checkpoint molecules and other drugs, the clinical success of viral vector applications in cancer therapy currently is limited. A number of challenges have to be solved to translate promising vectors to clinics. One of the key elements of successful virus-based cancer immunotherapy is the understanding of the tumour immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 237 publications
0
12
0
Order By: Relevance
“…In the context of clinical trials, a single administration of Ad26.COV2.S elicited rapid binding, neutralization antibody responses, and cellular immune responses in a phase I study in 25 healthy volunteers (Ricobaraza et al, 2020). Moreover, 1,045 healthy volunteers were vaccinated with a single dose of 1 × 10 10 or 5 × 10 10 Ad26.COV2.S particles in phase I/II study showed good safety and strong immune responses (Spunde et al, 2022).…”
Section: Non-human Adenovirus Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of clinical trials, a single administration of Ad26.COV2.S elicited rapid binding, neutralization antibody responses, and cellular immune responses in a phase I study in 25 healthy volunteers (Ricobaraza et al, 2020). Moreover, 1,045 healthy volunteers were vaccinated with a single dose of 1 × 10 10 or 5 × 10 10 Ad26.COV2.S particles in phase I/II study showed good safety and strong immune responses (Spunde et al, 2022).…”
Section: Non-human Adenovirus Vaccinesmentioning
confidence: 99%
“…Several human adenovirus serotypes were widely distributed and infected the majority of infants and young children in the early stages of their lives (Ricobaraza et al, 2020). According to several studies, 45% to 80% of persons had antibodies that neutralized AdHu5 viruses (Spunde et al, 2022). Depending on the location where they live, 5-15% of adults had virusneutralizing antibodies to AdHu 35.…”
Section: Adenovirus Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are considered the most adapted and clinically developed vectors. On the other hand, their use is limited in clinical practice due to the possibility of non-specific vector integration and insertional mutagenesis of any viral DNA vector [ 38 , 39 ]. The use of RNA viruses, despite their many attractive properties, is limited due to the complexity of genetic manipulations even with modern genetic technologies [ 40 ].…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…Often, a viral drug is administered intratumorally, but due to the need to treat metastases, it becomes necessary to administer it systemically. However, replication-competent viral vectors are best administered for local intratumoral administration in order to reduce toxicity, while replication-deficient vectors having proposed tumor affinity can be used for systemic delivery [ 39 , 45 ]. For example, the extracellular enveloped virus, one of the two antigenically and structurally distinct infectious virions produced by the vaccinia viruses, is naturally resistant to antibody neutralization and complementarity and, therefore, could be used for systemic delivery [ 46 ].…”
Section: Oncolytic Virusesmentioning
confidence: 99%